Modulus Constrained Minimax Radar Code Design Against Target Interpulse Fluctuation - Xie, Zhuang; Xu, Zhou; Han, Sudan; Zhu, Jiahua; Huang, Xiaotao (IEEE transactions on vehicular technology, 2023)
In the presence of colored Gaussian disturbance, this paper considers the robust transmit code and receiver filter design against target interpulse fluctuation while guaranteeing the dynamic range and energy of the transmit code. Aiming at enhancing the worst-case Signal-to-Noise-Ratio (SNR) over a spherical set, the design is cast as a non-convex minimax problem. It is shown that the filter can be directly derived based on the strong max-min property of the objective function. Then, the semi-definite relaxation form of the resultant problem is proved to be hidden convex by exploiting the strong duality of the Quadratically-Constrained Quadratic Programming (QCQP) problem. Finally, the robust code-filter pair can be effectively synthesized based on a randomization scheme. At the analysis stage, numerical results are shown to highlight the superiority of the proposed design.